Liraglutide Promotes Natriuresis but Does Not Increase Circulating Levels of Atrial Natriuretic Peptide in Hypertensive Subjects With Type 2 Diabetes - Lovshin, Julie A.; Barnie, Annette; DeAlmeida, Ariana; Logan, Alexander; Zinman, Bernard; Drucker, Daniel J. (Diabetes care, 2015)
GLP-1 receptor (GLP-1R) agonists induce natriuresis and reduce blood pressure (BP) through incompletely understood mechanisms. We examined the effects of acute and 21-day administration of liraglutide on plasma atrial natriuretic peptide (ANP), urinary sodium excretion, office and 24-h BP, and heart rate (HR). Liraglutide or placebo was administered for 3 weeks to hypertensive subjects with type 2 diabetes in a double-blinded, randomized, placebo-controlled crossover clinical trial in the ambulatory setting. End points included within-subject change from baseline in plasma ANP, Nt-proBNP, office BP, and HR at baseline and over 4 h following a single dose of liraglutide (0.6 mg) and after 21 days of liraglutide (titrated to 1.8 mg) versus placebo administration. Simultaneous 24-h ambulatory BP and HR monitoring and 24-h urine collections were measured at baseline and following 21 days of treatment. Plasma ANP levels did not change significantly after acute (+16.72 pg/mL, P = 0.24, 95% CI [-12.1, +45.5] at 2 h) or chronic (-17.42 pg/mL, 95% CI [-36.0, +1.21] at 2 h) liraglutide administration. Liraglutide significantly increased 24-h and nighttime urinary sodium excretion; however, 24-h systolic BP was not significantly different. Small but significant increases in 24-h and nighttime diastolic BP and HR were observed with liraglutide. Body weight, HbA1c, and cholesterol were lower, and office-measured HR was transiently increased (for up to 4 h) with liraglutide administration. Sustained liraglutide administration for 3 weeks increases urinary sodium excretion independent of changes in ANP or BP in overweight and obese hypertensive patients with type 2 diabetes.